RELATIONSHIP BETWEEN SMOKING, ANGIOGRAPHIC SUBTYPES AND VASCULAR INVOLVEMENT IN PATIENTS WITH FIBROMUSCULAR DYSPLASIA - THE ARCADIA-POL STUDY. (June 2018) - Witowicz, H.; Warchol-Celinska, E.; Ziebka, J.; Paschalis-Purtak, K.; Pucilowska, B.; Florczak, E.; Rowinski, O.; Aniszczuk-Hybiak, A.; Kowalczyk, K.; Widecka, K.; Soltysiak, M.; Protasiewicz, M.; et al.
Abstract : Objective: To assess the relationship between smoking and angiographic subtypes and vascular involvement in patients with fibromuscular dysplasia (FMD) enrolled into ARCADIA-POL study. Design and method: Out of 250 patients enrolled into ARCADIA-POL study since January 2015 (instituted on the basis of Polish-French collaboration) we analyzed 183 patients with confirmed FMD in at least one vascular bed. A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ABPM, biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. For the purpose of this analysis we divided 183 patients into two groups according to the status – 79 ever smokers (current or ex-smokers) (66F, 13 M, mean age: 46.9 ± 12.9 years) and 104 non-smokers (84F, 20 M, mean age: 45.2 ± 16.5 years). Results: As we compared smokers to non-smokers we found no statistically significant differences between the groups in age, gender, hypertension status (94.9% vs 87.5%, p = 0.086, respectively), nor in blood pressure values. Both groups did not also differ in terms of localization of vascular beds, nor number of vascular beds affected with FMD lesions. The most frequently FMD lesions were present in renal arteries (89.9% vs 82.7%, p = 0.17, respectively). There were also no differences between smoker and non-smoker in the number of vascular complications such as dissections (7.6% vs 8.7%, p = 0.79, respectively) and aneurysms (35.4% vs 28.8%, p = 0.34). In further analysis we also analyzed 41 FMD patients currently smoking and compared them to the never smokers and similarly we did not find differences between the analyzed groups. We also analyzed separately 157 consecutive patients with renal FMD dividing them into smoking and non-smoking individuals. We found no differences in terms of angiographic subtypes of renal FMD, number of complication, nor number of patients with history or currently significant renal artery stenosis. Conclusions: Although smoking has been implicated as a potential contributing factor to the development of FMD we did not found the relationship between the smoking and vascular involvement and complications in patients with FMD.